The prevalence of Japanese-B-Encephalitis in different species in Indonesi - Sendow I; S Bahri; A Sarosa (Indonesian Center for Animal Research and Development (ICARD), 2000)
Japanese-B-Encephalitis (JE) is a zoonotic disease which is characterized by encephalitis, caused by JE virus. The situation of this disease has not been known in both animals and human in Indonesia. This paper reports serological finding using competitive - ELISA to evaluate 953 serum samples, comprised of chicken, ducks, cattle, goats, horses, dogs, pigs and human from different areas in Indonesia. The antibody against JE virus was detected in animals and human sera, with prevalence varied among species and location. Cattle showed the highest prevalence of reactor (51 %) while pigs, dogs and horses had the lowest reactor (11%,12% and ]4%). The highest prevalence of reactor in cattle was found in North Sumatera (86%) and the lowest was found in West Java (23%). In goat, the highest prevalence of reactor was found in West Kalimantan (59%) and the lowest was detected in South Sulawesi (14%). Antibody against JE virus was also detected in chicken with the highest prevalence in North Sumatera and West Kalimantan (44%) and the lowest was in South Sulawesi (36%). The highest percentage of reactor in pigs was detected in South Sulawesi (50%) and the lowest was detected in West Kalimantan (2%). In human, the highest prevalence of reactor was found in West Kalimantan (30%) and the lowest was fowld in Irian Jaya. This result provide more information for further research, therefor the JE cases in Indonesia and its social, economic and psychological impacts can be anticipated as earlyas possible. Key words: Japanese-B-Encephalitis, antibody, animals, human, ELISA